An Increase of the Indonesian Throughflow by Internal Tidal Mixing in a High‐Resolution Quasi‐Global Ocean Simulation - H. Sasaki; S. Kida; R. Furue; M. Nonaka; Y. Masumoto (Geophysical Research Letters, 2018)
Abstract The impact of internal tidal mixing on the volume transport of the Indonesian Throughflow (ITF) is examined by a comparison of high‐resolution quasi‐global ocean simulations with and without a tidal mixing scheme. The ITF transport is found to be increased in the presence of tidal mixing. This is because tidal mixing decreases the density within and below the lower thermocline and increases the buoyancy of the water column. As a result, the surface pressure and the sea surface height (SSH) are raised. The magnitude of the SSH increase is larger for the tropical Pacific Ocean than for the other basins, possibly because many islands exist in the tropical Pacific and tidal mixing is effective around their shallow and rough topographies. Since SSH increases more in the tropical Pacific than in the Indian Ocean, the pressure difference between the two basins is enhanced and thus the ITF transport is strengthened.